The role of the private attorney in the Intermediate Stage of the Criminal Process - Rojas Jiménez, Karen Liliana (2024)
The objective of this article was to determine the assessment standards that made it possible to manifestly demonstrate an impact on the right of defense, with the purpose of granting justice operators the power to untimely admit the written acquittal of the accusatory requirement and what is established in article 350 paragraph 1 of the CPP. Establishing clear criteria for the right to defense was considered essential to ensure a fair trial. This right sought to protect the accused from the punitive power of the State through material and technical defense, the latter being exercised by a defense attorney. The approach is qualitative with a transversal, descriptiveexplanatory, dogmatic-prepositive research design with a projective nature. The results obtained expressed the need for our research proposal to approve a bill that was to propose concrete measures aimed at improving the performance of the private lawyer in the intermediate stage and, therefore, the quality of the defense. Finally, the investigation concluded that it was essential to guarantee fundamental rights such as the presumption of innocence and due process. To adequately confront the accusations, the accused should have been informed of the charges and had the assistance of a legal expert to represent and advise him.